Design Considerations in Enhancing Recreational Therapy in Long-Term Care - Literature Review - Moshchenskaya, Alesya; Trudel, Chantal; Attef, Maryam; Orosz, Zsofia (Proceedings of the International Symposium of Human Factors and Ergonomics in Healthcare, 2025)
In long-term care (LTC) homes, recreational therapy is vital in enhancing residents’ well-being. A review of literature explored the relationship between design and recreational therapy in LTC. This paper outlines case studies, challenges in implementation, impact, and suggestions for the future, resulting in a framework to inform how design strategies in recreational therapy may improve quality of life for residents in LTC.